Dynamic behaviour and measurement accuracy of a bicycle brake hood force transducer - Caya, A.; Champoux, Y.; Drouet, J. -M. (Procedia Engineering, 2012)
To measure road bike load inputs, it is customary to manufacture and instrument a bike component. The purpose of this paper is to investigate the influence of the dynamic behaviour of a brake hood force transducer on measurement accuracy. The majority of the studies reported in the literature on the development of transducers were designed with the objective of having high transducer stiffness in order to increase its first natural frequency to the highest possible degree. This paper shows that, in the case of force transmitted at cyclist's hands, this objective does not lead to the desired results. Rather, the best results are obtained when the natural frequency of the instrumented fabricated component matches that of its standard counterpart.